MODAL SOSIAL DALAM PEMANFAATAN BUAH TENGKAWANG DI HUTAN ADAT PIKUL - Dewita Dewita; Emi Roslinda; Siti Masitoh Kartikawati (Universitas Tanjungpura, 2020)
Pikul customary forest has the potential of tengkawang that was abundant and utilized by the community around the forest to fulfill their daily needs. This study aimed to determine community social capital consists of cognitive and structural social capital and the relationship of social capital how to use tengkawang fruit in the Pikul indigenous forest. This study used the concept survey methods, with data collection techniques with interviews used questionnaires and in-depth interviews with key respondents. Respondents in this study were Melayang Hamlet community who used tengkawang fruit intentionally. The magnitude level of social capital used the value interval equation and the relationship of social capital was analyzed of Sperman rating coefficient test. The results showed the cognitive social capital and the structural social capital were both classified as